Gellan Gum-based luminal fillers for peripheral nerve regeneration: an in vivo study in the rat sciatic nerve repair model. (21st February 2018) - Carvalho, C. R.; Wrobel, S.; Meyer, C.; Brandenberger, C.; Cengiz, I. F.; López-Cebral, R.; Silva-Correia, J.; Ronchi, G.; Reis, R. L.; Grothe, C.; Oliveira, J. M.; Haastert-Talini, K.
Abstract : This experimental work considers the innovative use of the biomaterial Gellan Gum (GG) as a luminal filler for nerve guidance channels. Abstract : Peripheral nerve injuries (PNI) resulting in a gap to be bridged between the transected nerve ends are commonly reconstructed with autologous nerve tissue, but there is a need for valuable alternatives. This experimental work considers the innovative use of the biomaterial Gellan Gum (GG) as a luminal filler for nerve guidance channels made from chitosan with a 5% degree of acetylation. The engineered constructs should remodel the structural support given to regenerating axons by the so-called bands of Büngner. Four different GG formulations were produced by combining varying amounts of High-Acyl GG (HA-GG) and Methacrylated GG (MA-GG). The effective porosity of the freeze-dried networks was analysed by SEM and micro-CT 3D reconstructions, while the degradation and swelling abilities were characterized in vitro for up to 30 days. The metabolic activity and viability of immortalized Schwann cells seeded onto the freeze-dried networks were also evaluated. Finally, the developed hydrogel formulations were freeze-dried within the chitosan nerve guides and implanted in a 10 mm rat sciatic nerve defect. Functional and histomorphological analyses after 3, 6, and 12 weeks in vivo revealed that although it did not result in improved nerve regeneration, the NGC25:75 formulations could provide a basis for further development of GG scaffolds as luminal fillers for hollow nerve guidance channels.